Discovering the invisible internet: methodological aspects of searching religion on the internet - Krüger, Oliver (Online - Heidelberg journal of religions on the internet, 2005)
Oliver Krüger discusses some empirical problems of Internet research in his contribution. Analysis of online discussion groups within the Wiccan and neopagan movement that refer to rituals indicates that new social and hierarchical structures also emerge within the ”online community”. Nonetheless, only subsequent interviews with users of those discussion forums could reveal some basic aspects of online communication and its social dimension. This gives rise to some further questions. How much can we tell about communication on religious Web sites? What are the limits of an immanent analysis of Web sites? What can we tell about social structures within online communities and about individual user preferences in a ritual discourse? How can we deal with the problem of identity of Internet users? What is empirically invisible for us? Acknowledging the limits of our conclusions on postmodern religion and religious people derived purely from online research, Krüger advocates combining online research with classical empirical fieldwork, such as quantitative surveys or qualitative interviews with users and Webmasters.